When and How to treat bruxism in children? - A review of the latest literature - Jerzak, Aneta; Jakubowska, Katarzyna; Janocha, Aleksandra; Ziemba , Paweł (Quality in Sport, 2024)
Introduction and purpose Bruxism is a stereotypical motor disorder characterized by involuntary grinding or clenching of the teeth during sleep or wakefulness. Bruxism affects 5-50% of children, and its frequency decreases with age. Bruxism is the most commonly occurring parasomnia, which in healthy individuals is a variant of physiology; however, when it leads to the development of associated pathologies such as dental abrasions, tooth loss, toothaches, headaches, or temporomandibular disorders, it is an indication for treatment. Materials and methods The literature included in the PubMed databases is searched through the words such as bruxism, temporomandibular disorder. Description of the state of knowledge In the diagnosis of bruxism, questionnaires filled out by patients and parents of children are most commonly used, although the most effective but less accessible diagnostic test is polysomnography. In the treatment of bruxism, pharmacotherapy, occlusal splints, and physiotherapy are used. Conclusions There is no gold standard for treating bruxism. There is still a need to search for other methods that would eliminate bruxism and prevent the development of associated pathologies.